CORRELATION BETWEEN LEUKOCYTE COUNT WHEN ADMITTED IN EMERGENCY ROOM (ER) WITH CLINICALLY ACUTE ISCHEMIC STROKE PATIENTS - Husna, Machlusil; Kusworini, Kusworini; Wulansari, Dian Ayu (Malang Neurology Journal, 2015)
Background. Stroke is a local or extensive disorder of brain function that occurs suddenly and rapidly, can cause death without another cause except vascular. Based on pathophysiology of acute ischemic stroke, leukocytes play an important role against deterioration and clinical manifestations in patients by releasing three inflammatory mediators, plugging mechanism in microcirculation, and vasoconstriction. Objective. To investigate the relationship between the clinical manifestations of acute ischemic stroke (incoming, outgoing, and improvement) as measured by the NIHSS score with the number of leukocytes . Methods. The study design was a retrospective cohort sampling. Samples were taken from 62 patients with acute ischemic stroke (31 patients who have normal leukocytes and 31 patients who showed leukocytosis) in Dr. Saiful Anwar (RSSA) Malang hospital that met the inclusion criteria of the study.Results. The results of the statistical test used is Kolmogorov-Smirnov test for incoming NIHSS (p = 0.999), and Chi-Square Test for outcoming NIHSS (p = 0.000) and improved patient (p = 0.001).Conclusion. Patients who have normal leukocyte count at the beginning of treatment is likely to have clinical manifestations by category of incoming NIHSS similar to patients who showed leukocytosis, and tend to have clinical manifestations by category of outcoming NIHSS and improvement or significantly better than patients which showed leukocytosis.